Time and Entropy: The Two Sides of The Same Medal in Ideal Open Systems - Horst Josef Koch (Journal of Medical Physics and Biophysics, 2016)
The second thermodynamic law implies a continuous  increase of        entropy with time and a formal relation of both characteristics.        Based on observations in ideal biophysical diffusion processes the letter presents a    model that substantiates an exponential relationship            between time and entropy.